Staphylococcal superantigens in colonization and disease - Xu, Stacey X.; Mccormick, John (Frontiers in Cellular and Infection Microbiology, 2012)
Superantigens (SAgs) are a family of potent immunostimulatory exotoxins known to be produced by only a few bacterial pathogens, including Staphylococcus aureus. More than 20 distinct SAgs have been characterized from different S. aureus strains and at least 80% of clinical strains harbour at least one SAg gene, although most strains encode many. SAgs have been classically associated with food poisoning and toxic shock syndrome (TSS), for which these toxins are the causative agent. TSS is a potentially fatal disease whereby SAg-mediated activation of T cells results in overproduction of cytokines and results in systemic inflammation and shock. Numerous studies have also shown a possible role for SAgs in other diseases such as Kawasaki disease, atopic dermatitis, and chronic rhinosinusitis. There is also now a rich understanding of the mechanisms of action of SAgs, as well as their structures and function. However, we have yet to discover what purpose SAgs play in the life cycle of S. aureus, and why such a wide array of these toxins exists. This review will focus recent developments within the SAg field in terms of the molecular biology of these toxins and their role in both colonization and disease.